NUMERICAL STUDY OF ICE LAYER GROWTH AROUND A VERTICAL TUBE - Stampa, C. S.; Nieckeleb, A. O. (Revista de Engenharia Térmica, 2005)
Typical latent heat of fusion storage systems consists of vertical tubes inside a larger container, with phase change material being formed outside the tubes. During the charging stage of the cycle, ice is formed around the exterior of the tubes. Once all water has frozen, the discharging process can begin. This work presents a numerical investigation concerning the growth of an ice layer formed outside a vertical tube, inside an annular cavity. The inner wall of the cavity represents the external wall of the tube, whereas the outer one represents the limit of growth for the formed ice layer. Natural convection plays a significant role during the ice formation, especially due to density inversion behavior with temperature. To be able to control the growth of ice layers inside typical thermal energy storage devices, it is necessary to understand the phenomenum. The problem was solved two-dimensionally, making use of a model based on the finite volume method. The results are presented by means of: streamlines, representing the flow patterns driven by buoyancy forces; isolines of temperature; heat transfer at the inner wall of the cavity and the extraction of the thermal energy stored into the annular region of the cavity.